Difficulties Faced by Researchers in Participatory Practices: An Example of Research with Roma People - Mikulec, Marek; Glumbíková, Kateřina (Participatory Social Work: Research, Practice, Education, 2019)
The number of socially excluded localities and persons residing in them has significantly increased in the Czech Republic over the last ten years. Socially excluded localities have their specific characteristics and environment that very often concern exclusively the Roma localities. The participatory research aims to gain access to the locality followed by the establishment of communication and cooperation with local residents. These relationships, however, show a number of difficulties that in this contribution are reconstructed based on the ethnographic research conducted in a socially excluded locality inhabited by the Roma community. Some partial recommendations have been formulated for accessing the field. These are recommendations relating to the individual characteristics of the researcher, the specific characteristics of the environment and the characteristics of the target group (the Roma community).